Scagliola Interiors in Vienna 1800–1900: Material, Development and Conservation. (31st August 2020) - Fuchs, Katharina; Krist, Gabriela
ABSTRACT: In the Central European context the imitation of natural stone is called stucco marble or scagliola . During its manufacture, the mixture of gypsum, animal glue and pigments produces a marble-like structure and after several sanding and polishing processes it attains a glossy surface. Scagliola plays a significant role in the history of interior design in the eighteenth and nineteenth centuries in central Europe. Originally, it was used during the first half of the seventeenth century to imitate stone inlaid work, pietra dura, for table tops and as antependia . Scagliola interiors in the eighteenth century, the main period of use, have individual designs, colours and shapes. This technique was substituted for stone because coloured marble was expensive, and some types of natural stone have a limited colour range. In the first half of the nineteenth century, scagliola found little or no application, but it was rediscovered in the second half of the century. In Vienna, high-quality stucco marble was used extensively in public buildings or private palaces. Recent research is focusing on the interior of churches during the Baroque and Rococo periods in southern Germany. Studies on conservation methods for scagliola barely exist at an international level. In order to ensure the preservation of these valuable surfaces, a catalogue is being compiled of nineteenth-century scagliola works in Vienna, as well as an overview of recent and present conservation measures.